Body in twentieth-century Italian literature: Anna Maria Ortese’s case (Philology, 2022)
The question of the body as a construct in the Italian literary context has not been analysed in a systematic way. The ideological background that gave rise to the literary and aesthetic movements from the 1950s on has been continuously discussed. But we cannot say the same for the repetition of a previous culturally determined model, for observations of its change with a certain degree of ‘renovation’ influenced by the period. In addition, culture, which is directly shaped by the ideological and in close relation to the literary, according to the perception of the social psychologist Hofstede, is understood as ‘collective programming of the mind’ (Hofstede, 1984). The present study aims to make an interdisciplinary reading of the body in the novels of the Italian writer Anna Maria Ortese. The concept will be regarded as a literary, philosophical and social notion. The oppositions individualism – collectivism, high – low power distance, security – insecurity, masculinity – femininity, long-term – short-term time orientation, and satisfaction – dissatisfaction will be analyzed with regard to the identity, strengthening it through repetition. The research question is whether the human body in literature, and in particular that of the main characters in Italian novels during the second half of the XX century, represented through Anna Maria Ortese’s work, is a repetition of the stereotyped model, what is the degree of renewal that distinguishes it, and whether parallels can be made between the construct in the Italian literary plan and in others.
Keywords: body; power; ideology; Italian literature; relations; paradigm